The relationship between processed meat, red meat, and risk of types of cancer: A Mendelian randomization study - Wu, Kaiwen; Liu, Lei; Shu, Tao; Li, Aoshuang; Xia, Demeng; Sun, Xiaobin (Frontiers in Nutrition, 2022)
Background: Observational studies have suggested processed meat and red meat may increase the risk of cancer. We conducted a two sample Mendelian randomization (MR) study to assess the associations of processed meat and red meat with eight types of cancer in the general population. However, the causal effects and direction between them were still unclear. Method: Genome-Wide Association Studies (GWAS) for processed meat and red meat (pork, beef and mutton) were obtained from the UK Biobank. GWAS of eight cancers we studied extracted from the genetic consortia and the FinnGen consortium. The inverse variance weighted (IVW) method was proformed as the main method for two sample MR analysis. Sensitivity analysis was used to assess the robustness of the results. Result: Genetically predicted consumption of processed meat was causally associated with an increased risk of lung cancer (IVW: OR 1.923, 95%CI: 1.612-2.294, P=0.025 in processed meat). There is no convincing evidence for the associations between genetically determined processed meat, red meat and the risk of other cancers we studied. Conclusion: This sutdy suggested that intake of processed meat may increase the risk of lung cancer. These findings provided no evidence to support that consumption of processed and red meat has a large effect on risk of other cancers we studied. Further research is needed to clarify the results.